1990
DOI: 10.1007/bf00370225
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in normal and potassium-depleted rats before and after preparation for micropuncture experimentation

Abstract: Renal function was examined in unrestrained conscious rats maintained on either a control diet or a low-potassium diet, then re-examined in the same animals after thiobutabarbital (Inactin) anaesthesia and preparation for micropuncture studies. In conscious rats, insulin clearance (CIn) was not significantly different in the two groups (control 1012 +/- 43, low-K 904 +/- 58 microliters/min per 100g body wt; mean +/- SE), but lithium clearance (CLi; used as an estimate of end-proximal fluid delivery) and fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…These values fall within the normal ranges for Sprague-Dawley rats as documented in this laboratory (e.g. Shirley et al 1990;Unwin et al 1994). …”
Section: Whole Animal Datasupporting
confidence: 84%
“…These values fall within the normal ranges for Sprague-Dawley rats as documented in this laboratory (e.g. Shirley et al 1990;Unwin et al 1994). …”
Section: Whole Animal Datasupporting
confidence: 84%
“…The present study revealed that NHE3 abundance in the proximal tubules and TALs of rat kidney was significantly increased. Consistent with the increased abundance of NHE3 in the proximal tubules, micropuncture studies have previously shown that potassium depletion in rats was associated with substantially reduced lithium clearance, indicating that sodium and water delivery to the end of the proximal tubules was reduced (43), possibly due to increased proximal tubular reabsorption in hypokalemia (47).…”
Section: Increased Nhe3 Abundance In Proximal Tubules and Tals In Hypmentioning
confidence: 54%
“…Sprague-Dawley rats or Munich-Wistar rats were anesthetized with sodium thiopentone (100 mg/kg, intraperitoneally; Link Pharmaceuticals, Horsham, Sussex, UK) and prepared surgically for micropuncture of the left kidney (12). All animals received intravenous infusions of isotonic saline at 4 ml/h.…”
Section: Methodsmentioning
confidence: 99%